Root growth-promoting effect in wheat plants exerted by Azospirillum argentinense REC3, its flagellar protein AZFLAP and a strawberry hydroalcoholic extract in a simple rhizotron system - Correa Deza, Maria Alejandra (2024)
Root research often uses rhizotron systems where their main characteristic is to possess a transparent wall allowing the in situ observation of plants’ root system. Rhizotrons can vary in size and be filled with different substrates based on soil, sand and other components. Here, a simple and low cost rhizotron system without soil substrate was developed, allowing the observation of wheat (Triticum aestivum L.) root system treated with bioproducts. To show the effectiveness of the rhizotrons, hydrated wheat seeds were treated with plant growthpromoting bioproducts such as Azospirillum argentinense REC3 (106 CFU.ml-1 ), flagellin AzFlap (200 nM), or strawberry hydroalcoholic extract (0.01 mg.mL -1 ). This rhizotron system allowed to non-destructively evaluate the roots (length, density and root hair proliferation), where the values of the bioproducts surpassed the control.